Indocyanine green intravenous administration can more accurately identify the intersegmental plane than the inflation-deflation method in lung segmentectomy - Takahiro Ochi; Yuichi Sakairi; Yuki Sata; Takahide Toyoda; Terunaga Inage; Kazuhisa Tanaka; Hajime Tamura; Masako Chiyo; Yukiko Matsui; Yuki Shiko; Masayuki Ota; Jun-ichiro Ikeda; et al. (PLoS ONE, 2025)
Background Indocyanine green (ICG) intravenous administration (ICG-iv) has been described for detecting the intersegmental plane in lung segmentectomy. However, errors with preoperative planning and accuracy comparisons with alternative methodologies have not been fully validated. Methods This single-center retrospective study identified 138 patients with 140 lesions who underwent segmentectomy using the inflation-deflation (I-D) method or ICG-iv method. The planned margin was calculated using three-dimensional imaging, and the surgical margin was measured for the resected specimen. We evaluated the surgical and planned margin ratio (S/P ratio) and log S/P ratio. Accuracy was also tested using the Root Mean Squared Logarithmic Error (RMSLE): the smaller the RMSLE, the more accurate. Results The study enrolled 86 patients with 88 lesions in the I-D group and 52 patients with lesions in the ICG-iv group. All lesions were completely resected. The ICG-iv group underwent significantly more complex segmentectomies compared to the I-D group (P < 0.001). The median S/P ratio was 0.886 (I-D) and 0.912 (ICG-iv). The mean log S/P ratio was −0.061 (I-D) and −0.013 (ICG-iv). The RMSLE values were 0.258 (I-D) and 0.229 (ICG-iv). In the ICG-iv group, eight patients with lesions (15.3%) had poor staining for intersegmental identification. Notably, the poor staining subgroup included a higher proportion of patients with obstructive pulmonary disease (4/8: 50.0%) compared to the good staining group (6/44: 13.6%) (P = 0.035). Conclusions The ICG-iv method demonstrated superior accuracy in identifying the intersegmental plane compared to I-D method; however, concerns persist regarding suboptimal staining in patients with obstructive pulmonary disease.